2020
DOI: 10.3389/fnut.2020.601329
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Interventions in Cancer Cachexia: Evidence and Perspectives From Experimental Models

Abstract: Cancer cachexia is a complex metabolic syndrome characterized by involuntary skeletal muscle loss and is associated with poor clinical outcome, decreased survival and negatively influences cancer therapy. No curative treatments are available for cancer cachexia, but nutritional intervention is recommended as a cornerstone of multimodal therapy. Optimal nutritional care is pivotal in the treatment of cancer cachexia, and the effects of nutrients may extend beyond provision of adequate energy uptake, targeting d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 160 publications
(200 reference statements)
1
43
0
1
Order By: Relevance
“…The routine assessment of body composition has also shown clinical significance for the treatment of cancer, specifically as it pertains to cachexia and lymphedema. Cancer cachexia falls under the umbrella of sarcopenia, where it is defined as a multifactorial syndrome that causes extreme weight loss and muscle wasting, with or without the loss of fat [ 31 , 32 ]. Cachexia can occur in up to 80% of patients with advanced stage cancer and has been associated with nearly 20% of cancer-related deaths [ 33 ].…”
Section: Clinical Relevance Of Body Composition Assessmentmentioning
confidence: 99%
“…The routine assessment of body composition has also shown clinical significance for the treatment of cancer, specifically as it pertains to cachexia and lymphedema. Cancer cachexia falls under the umbrella of sarcopenia, where it is defined as a multifactorial syndrome that causes extreme weight loss and muscle wasting, with or without the loss of fat [ 31 , 32 ]. Cachexia can occur in up to 80% of patients with advanced stage cancer and has been associated with nearly 20% of cancer-related deaths [ 33 ].…”
Section: Clinical Relevance Of Body Composition Assessmentmentioning
confidence: 99%
“…The safety of long-term creatine supplementation in both healthy individuals and patients has been well documented, which provides a clear and expedient path forward for utilizing creatine supplementation to treat cancer [ 13 , 64 , 96 , 97 , 98 , 99 ]. Additionally, creatine supplementation can augment muscle and enhance strength, which may also benefit cancer patients suffering from cachexia at their late stages [ 63 , 64 , 100 , 101 ]. Both oral and intravenous administration routes can be effective in animal tumor models [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that creatine supplementation can function as an adjunctive therapeutic intervention with other anticancer agents. Moreover, given the beneficial effects of creatine on muscle mass and physical function, emerging evidence has suggested that creatine supplementation may also have therapeutic potential for attenuating cancer-related weight loss and maintaining muscle function for cancer patients [ 63 , 64 ]. However, application in various cancer contexts has just began and further studies are needed to fully understand the impact of creatine supplementation on clinical outcomes in the cancer patient population at a risk of muscle wasting.…”
Section: Creatine Supplementation For Cancer Therapy—other Potential Benefitsmentioning
confidence: 99%
“…These factors may explain the relatively strong correlation between muscle loss and mortality. Although cancer cachexia cannot be treated with nutritional therapy alone, optimal nutritional care is recommended as a cornerstone of multimodal therapy (39). Getting enough dietary protein is a prerequisite for the maintenance or gain of skeletal muscle mass (40), whereas, the muscle wasting associated with cancer is troublesome and cannot be completely reversed with enhanced nutritional support (1).…”
Section: Discussionmentioning
confidence: 99%